Efektivitas Bermain Pada Masa Pendidikan Anak Usia Dini di PAUD Al-Mahir - Purnamasari, Rasti; Nasution, Leni Masnidar; YM, Khairuddin (AUD Cendekia: Journal of Islamic Early Childhood Education, 2021)
Early  childhood  education  is  very  meaningful  for  child development.  The  method used  must  be  in  accordance  with  the  child's  development, the method used is playing. The reality is that in children's  life   it   is   inseparable   from   playing,   from   playing   children   to   get  extraordinary  experiences.  This  research  was  conducted  in  a  qualitative form. The purpose of this paper is to determine the effectiveness of play in  early  childhood  education.  The  results  of  this  study  are  proven  that playing can affect early childhood education